Thermostability enhancement of the α-carbonic anhydrase from Sulfurihydrogenibium yellowstonense by using the anchoring-and-self-labelling-protein-tag system (ASLtag). (1st January 2019) - Del Prete, Sonia; Merlo, Rosa; Valenti, Anna; Mattossovich, Rosanna; Rossi, Mosè; Carginale, Vincenzo; Supuran, Claudiu T.; Perugino, Giuseppe; Capasso, Clemente
Abstract: Carbonic anhydrases (CAs, EC 4.2.1.1) are a superfamily of ubiquitous metalloenzymes present in all living organisms on the planet. They are classified into seven genetically distinct families and catalyse the hydration reaction of carbon dioxide to bicarbonate and protons, as well as the opposite reaction. CAs were proposed to be used for biotechnological applications, such as the post-combustion carbon capture processes. In this context, there is a great interest in searching CAs with robust chemical and physical properties. Here, we describe the enhancement of thermostability of the α-CA from Sulfurihydrogenibium yellowstonense ( Ss pCA) by using the anchoring-and-self-labelling- protein-tag system (ASL tag ). The anchored chimeric H 5 - Ss pCA was active for the CO2 hydration reaction and its thermostability increased when the cells were heated for a prolonged period at high temperatures (e.g. 70 °C). The ASL tag can be considered as a useful method for enhancing the thermostability of a protein useful for biotechnological applications, which often need harsh operating conditions. Graphical Abstract: